2010
DOI: 10.1155/2010/948543
|View full text |Cite
|
Sign up to set email alerts
|

Nona-Arginine Facilitates Delivery of Quantum Dots into Cells via Multiple Pathways

Abstract: Semiconductor quantum dots (QDs) have recently been used to deliver and monitor biomolecules, such as drugs and proteins. However, QDs alone have a low efficiency of transport across the plasma membrane. In order to increase the efficiency, we used synthetic nona-arginine (SR9), a cell-penetrating peptide, to facilitate uptake. We found that SR9 increased the cellular uptake of QDs in a noncovalent binding manner between QDs and SR9. Further, we investigated mechanisms of QD/SR9 cellular internalization. Low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…The safety of most CPPs has been confirmed in a detailed metabolic analysis (Kilk et al, 2009). Our previous results demonstrated that CPPs do not cause cytotoxicity in cells as indicated by trypan blue (Chang et al, 2005aDai et al, 2011a;Hou et al, 2007;Wang et al, 2006Wang et al, , 2007, 1-(4,5-dimethylthiazol-2-yl)-3,5-diphenylformazan (MTT) (Chen et al, 2012;Hou et al, 2007;Wang et al, 2007), 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) (Xu et al, 2010), and sulforhodamine B (SRB) (Hu et al, 2009;Lee et al, 2011;Liu et al, 2010aLiu et al, , 2011 assays. Recently, detailed studies reported that CPPs are nontoxic and nonimmunogenic in vitro and in vivo (Suhorustsenko et al, 2011).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The safety of most CPPs has been confirmed in a detailed metabolic analysis (Kilk et al, 2009). Our previous results demonstrated that CPPs do not cause cytotoxicity in cells as indicated by trypan blue (Chang et al, 2005aDai et al, 2011a;Hou et al, 2007;Wang et al, 2006Wang et al, , 2007, 1-(4,5-dimethylthiazol-2-yl)-3,5-diphenylformazan (MTT) (Chen et al, 2012;Hou et al, 2007;Wang et al, 2007), 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) (Xu et al, 2010), and sulforhodamine B (SRB) (Hu et al, 2009;Lee et al, 2011;Liu et al, 2010aLiu et al, , 2011 assays. Recently, detailed studies reported that CPPs are nontoxic and nonimmunogenic in vitro and in vivo (Suhorustsenko et al, 2011).…”
Section: Discussionmentioning
confidence: 60%
“…The recent identification of nontoxic cell-penetrating peptides (CPPs) has led to the development of a new nonviral technology for delivering biological macromolecules (Deshayes et al, 2010;Gump and Dowdy, 2007) and nanomaterials (Liu et al, 2010a(Liu et al, , 2010b(Liu et al, , 2011Xu et al, 2010) into live cells. CPPs, also known as protein transduction domains, are a group of short cationic peptides originally derived from a viral protein (Frankel and Pabo, 1988;Green and Loewenstein, 1988;Gump and Dowdy, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Covalently linking QDs and CPPs is a lengthy process that requires purification and chemical identification. Our studies have demonstrated that noncovalent linking is effective, inexpensive and relatively easy [15,24,25].…”
Section: Introductionmentioning
confidence: 81%
“…However, QDs alone do not readily enter cells, and aggregation often occurs after internalization [19,20]. To overcome these limitations, surface modified QDs functionalized by covalent [21e23] or noncovalent [15,24,25] linkages with CPPs, denoted as CPP-QDs or CPP/QDs respectively, have been introduced recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation